SEX EDUCATION IN ELEMENTARY SCHOOL TO PREVENT SEXUAL ABUSE OF CHILDREN - G. A Bunga Azani Putri (PROGRES PENDIDIKAN, 2022)
Cases of sexual abuse in children are increasing every year so it is necessary to prevent one of them through sex education in elementary schools. Sex education is an effort to teach, raise awareness, and provide information about sexual problems. Sex education for children can also prevent children from becoming victims of sexual harassment, by being equipped with knowledge about sex, they will understand which behaviors are classified as sexual harassment. With the literature review method using various sources of research results that have been carried out, the contents of which are trying to find a picture of the need for sex education in elementary schools to prevent sexual abuse in children.